Sperm morphology and chromatin integrity in Swedish warmblood stallions and their relationship to pregnancy rates - Sandebert Thomas; Hammar Linda; Johannisson Anders; Dalin Anne-Marie; Morrell Jane M; Rodriguez-Martinez Heriberto (Acta Veterinaria Scandinavica, 2008)
Abstract Background Artificial insemination is not as widely used in horses as in other domestic species, such as dairy cattle and pigs, partly because of the wide variation in sperm quality between stallion ejaculates and partly due to decreased fertility following the use of cooled transported spermatozoa. Furthermore, predictive tests for sperm fertilising ability are lacking. The objective of the present study was to assess sperm morphology and chromatin integrity in ejaculates obtained from 11 warmblood breeding stallions in Sweden, and to evaluate the relationship of these parameters to pregnancy rates to investigate the possibility of using these tests predictively. Methods Aliquots from fortyone ejaculates, obtained as part of the normal semen collection schedule at the Swedish National Stud, were used for morphological analysis by light microscopy, whereas thirtyseven were used for chromatin analysis (SCSA) by flow cytometry. The outcome of inseminations using these ejaculates was made available later in the same year. Results Ranges for the different parameters were as follows; normal morphology, 27–79.5%; DNA-fragmentation index (DFI), 4.8–19.0%; standard deviation of DNA fragmentation index (SD_DFI) 41.5–98.9, and mean of DNA fragmentation index (mean_DFI), 267.7–319.5. There was considerable variation among stallions, which was statistically significant for all these parameters except for mean_DFI (P < 0.001, P < 0.01, P < 0.001 and P < 0.2 respectively). There was a negative relationship between normal morphology and DFI (P < 0.05), between normal morphology and SD_DFI (P < 0.001), and between normal morphology and mean_DFI (P < 0.05). For specific defects, there was a direct relationship between the incidence of pear-shaped sperm heads and DFI (P < 0.05), and also nuclear pouches and DFI (P < 0.001), indicating that either morphological analysis or chromatin analysis was able to identify abnormalities in spermiogenesis that could compromise DNA-integrity. A positive relationship was found between normal morphology and pregnancy rate following insemination (r = 0.789; P < 0.01) and a negative relationship existed between DFI and pregnancy rate (r = -0.63; P < 0.05). Sperm motility, assessed subjectively, was not related to conception rate. Conclusion Either or both of the parameters, sperm morphology and sperm chromatin integrity, seem to be useful in predicting the fertilising ability of stallion ejaculates, particularly in determining cases of sub-fertility.